Environmental and Closure Costs in Strategic Mine Planning, Models, Regulations, and Policies - David Oliveros-Sepúlveda; Marc Bascompta-Massanés; Giovanni Franco-Sepúlveda (Resources)
This study explores the evolution of mine planning, with particular emphasis on the integration of environmental and social factors in alignment with the sustainable development. Traditionally, mine planning emphasized technical and economic variables, often overlooking environmental and social impacts. However, the increasing need to align with the Sustainable Development Goals (SDGs) has prompted a shift toward broader definitions that incorporate these factors into resource planning. This paradigm change is crucial for managing risks related to project profitability, which now include environmental considerations. The article also examines how government policies and corporate strategies, including Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) frameworks have evolved to address these impacts. A review of the literature published over the last 25 years identifies four main thematic areas: (1) inclusion of environmental costs in mine planning, (2) quantitative models for calculating environmental and closure costs, (3) legal frameworks in mining, and (4) innovations in public policies. This study underscores the need for a comprehensive approach in mine planning that balances economic, social, and environmental considerations to ensure sustainability and mitigate risks associated with mine closure and environmental remediation.